SPEECH ACTS USED BY THE HUSBAND AND WIFE IN THE RECONCILIATION PROCESSES IN “NOT EASILY BROKEN” - Linda Yuniarti; Henny P.S. Wijaya (Kata Kita: Journal of Language, Literature, and Teaching, 2013)
The writer researches the language use of husband and wife in their reconciliation processes and its connection to the reconciliation processes. She uses a film, entitled “Not Easily Broken” (2009) as the representative of reconciliation of husband and wife. She researches the Speech Act of Dave and Clarice during their reconciliation processes. The writer uses the Speech Act theory (Austin, 1962; Searle, 1969; Yule, 1996) and the reconciliation process (Huyse, 2003). Inthe findings of the research, the highest illocution is ‘Representative’ and automatically, the highest perlocution is from ‘Representative’. In the first and second stages, most of the perlocution does not match but in the last stage, all perlocutions match to the illocution and the reconciliation is accomplished.The conclusion is a couple should accept the fact and truth to each other to accomplish reconciliation process.